Morphometric study of Phragmatopoma caudata (Polychaeta: Sabellida: Sabellariidae) - Occhioni,Gisele E. (2009)
The sabellariid Phragmatopoma caudata (Kroyer, 1856), Morch, 1863 is widely distributed in the Americas and constructs large reef agglomerates that provide substrates for other benthic species. However, the difficulty in obtaining size data (especially length) hampers population studies, making it necessary to carry out morphometric studies as basis for studies of population dynamics. The objective of the present study is to determine the best morphological descriptor of length in P. caudata. A total of 17 morphometric variables were measured in specimens from four different populations. Measurements were performed using an ocular micrometer attached to a stereoscopic microscope. Correlations in the dataset were tested using Pearson's linear correlation coefficient, and the hypothesis of morphometric differences among populations was tested using MANOVA and principal component analysis. Correlation coefficients were different amongst populations, as well as in the measured traits . Moreover, the results suggest that populations differ more strongly in body size than in shape. Although populations presented different morphometric relationships, the length of the first thoracic chaetiger was one of the variables with highest correlation with total length. This result, as well as the fact that such region is located on the anterior portion of the body, suggests that this structure is a good length descriptor in P. caudata.